A genome‐wide linkage map for the house sparrow (Passer domesticus) provides insights into the evolutionary history of the avian genome. (31st January 2020) - Hagen, Ingerid J.; Lien, Sigbjørn; Billing, Anna M.; Elgvin, Tore O.; Trier, Cassandra; Niskanen, Alina K.; Tarka, Maja; Slate, Jon; Sætre, Glenn‐Peter; Jensen, Henrik
Abstract: The house sparrow is an important model species for studying physiological, ecological and evolutionary processes in wild populations. Here, we present a medium density, genome wide linkage map for house sparrow ( Passer domesticus ) that has aided the assembly of the house sparrow reference genome, and that will provide an important resource for ongoing mapping of genes controlling important traits in the ecology and evolution of this species. Using a custom house sparrow 10 K iSelect Illumina SNP chip we have assigned 6, 498 SNPs to 29 autosomal linkage groups, based on a mean of 430 informative meioses per SNP. The map was constructed by combining the information from linkage with that of the physical position of SNPs within scaffold sequences in an iterative process. Averaged between the sexes; the linkage map had a total length of 2, 004 cM, with a longer map for females (2, 240 cM) than males (1, 801 cM). Additionally, recombination rates also varied along the chromosomes. Comparison of the linkage map to the reference genomes of zebra finch, collared flycatcher and chicken, showed a chromosome fusion of the two avian chromosomes 8 and 4A in house sparrow. Lastly, information from the linkage map was utilized to conduct analysis of linkage disequilibrium (LD) in eight populations with different effective population sizes (Ne ) in order to quantify the background level LD. Together, these results aid the design of future association studies, facilitate the development of new genomic tools and support the body of research that describes the evolution of the avian genome.